CONGENITAL INTESTINAL MALROTATION WITH CO-EXISTENT JEJUNAL DIVERTICULA IN A SEPTUAGENARIAN MALE: A CASE REPORT (Journal of Medical & Health Sciences Review, 2025)
Introduction: Intestinal malrotation is a congenital anomaly with mostly reported cases in neonates, although in adults limited cases have been reported in the literature. However, in adults prompt recognition is of utmost importance to prevent drastic complications like bowel ischemia and death. We present a rare case of coexistence of congenital intestinal malrotation and jejunal diverticula presenting as a volvulus.Case presentation: We present a case of 78 year old male with no comorbidities presenting to emergency department with acute abdomen , diagnosed as a case of intestinal obstruction in a virgin abdomen  , treated conservatively. Meanwhile CT abdomen and pelvis showed volvulus of small intestine, so patient was taken for exploratory laparotomy which has evidenced the small bowel rotation with high cecum and narrow mesentery, Ladd’s procedure was performed without any per operative complications.Discussion: Few reports of congenital intestinal malrotation in elderly are presented in literature. This highlights the importance of evaluating all patients for malrotation if presenting in elderly patients with virgin acute abdomen to prevent complications like bowel ischemia.Conclusion: Elderly patients presenting with acute intestinal obstruction if not improving conservatively, should make the clinician think about congenital intestinal malrotation as a differential diagnosis as well, among all other common causes.